Hair care practices and structural evaluation of scalp and hair shaft parameters in African American and Caucasian women. (24th August 2015) - Lewallen, Robin; Francis, Shani; Fisher, Brian; Richards, Jeanette; Li, Jim; Dawson, Tom; Swett, Katrina; McMichael, Amy
Summary How African American hair fragility relates to hair care practices and biologic differences between races is not well understood. To assess the differences between perceptions of hair health, hair care practices, and several biologic hair parameters between Caucasian and African American women. A questionnaire on perceptions of hair health and hair care practices was administered. Biological and structural parameters of hair shaft and scalp, including growth, density, diameter, cycle, breakage, and scalp blood flow were also assessed in this case–control study. Significant differences between the Caucasian and African American women were observed in the questionnaire and biologic study data. Regarding self‐reported perceptions of hair health, there were differences in the following: hair shaft type (P < 0.001), hair breakage (P = 0.040), and desire to change hair (P = 0.001). Regarding self‐reported hair care practices, there were differences in the following: location of haircutting (P = 0.002) and washing (P = 0.010), washing frequency (P < 0.001), chemical relaxer use (P < 0.001), hooded hair dryer use (P < 0.001), and hair shaft conditioner use (P = 0.005). The two groups had similar practices in regard to the use of hair color, frequency of hair color use, chemical curling agents, and handheld blow dryer use. Regarding biological and structural parameters, there were differences in the following: hair growth rate (P < 0.001), density (P = 0.0016), diameter (P = 0.01), number of broken hairs (P < 0.001), and blood flow (P = 0.03). There was no significant difference in hair cycle parameters.The differences in hair care practices and hair fiber morphology among African American women may contribute to clinically observed variation in hair fragility and growth.